Tourism community relationships - Pearce, Philip L. (Tourism social science series, 1996)
The study of tourism is, arguably, ready for a thorough theoretical yet empirical analysis of the relationship between tourism and host communities. Pearce, Moscardo and Ross deal with the impacts tourism is having on communities internationally, going beyond a mere review of such impacts to investigate the origins, development and manifestations of community attitudes. A theoretical perspective is developed on how communities come to understand tourism and react to it. In terms of its disciplinary approaches the book combines social-psychological, sociological, economic and media analyses and can properly be termed a study within the new "specialism" of tourism. A number of yet-to-be published studies of tourism and communities are reported on, and some large scale existing works on tourism and community reaction are reviewed and revisited.